Exploring participant experiences of research after traumatic brain injury. (June 2014) - Theadom, Alice; Fadyl, Joanna; Hollands, Tania; Foster, Allison; McPherson, Kathryn M.
Abstract Objective: To explore peoples' perceptions and experiences of taking part in research following a traumatic brain injury (TBI) and identify the factors that influence research participation. Methods: A total of 30 people (15 who had participated in research following a TBI and 15 who had previously declined or not been offered the opportunity to take part), were asked about their perceptions and experiences of research in a semi-structured qualitative interview. Audio recordings of the interviews were transcribed verbatim and analysed using the qualitative description approach. Results: Participants perceptions and experiences of research were strongly influenced by the researcher, the practicalities of taking part, including the timing and relevance of research, and perceived end results, such as access to a new treatment or reimbursement for their time. Conclusion: People want to be empowered to make their own decisions about research participation following a TBI. The findings have implications for research procedures and researchers working in the field of brain injury and recommendations to enhance the research experience are proposed.